Upaya G20 Dalam Mendorong Pemulihan Ekonomi Kawasan Southern Hemisphere Pasca Pandemi Covid-19 - Siti Nurjannah; Aurelia Putri Noveri; Nanda Putri Khalifah; Ida Susilowati (JOURNAL of LEGAL RESEARCH, 2022)
Coronavirus Disease 2019 (COVID-19) has become a terrible pandemic and has an impact on the global economic crisis, including the southern hemisphere. Solidarity, collaboration and cooperation among southern countries are demands in fighting the economic crisis due to the Covid-19, one of which is through the G-20. This is shown by the G20 in the theme carried out in 2022, namely “Recover together, recover stronger” through strengthening global solidarity. This study aims to analyze the efforts of the G20 in encouraging the economic recovery of the southern hemisphere countries, during the Covid-19 pandemic. Descriptive-qualitative research method is used in analyzing the issue, accompanied by data collection techniques through literature study. The results of this study indicate that the G20 has attempted several ways to encourage post-pandemic economic recovery in the southern hemisphere, through: International Financial Architecture, Financial Sector Reform, Sustainable Finance. Infrastrukture, and International Taxation